O pensamento geográfico presente nas obras de Júlio Verne : um ensaio sobre o ensino da Geografia na sala de aula - Pinto, Ariane Bastos Lara (2019)
The pedagogical methodologies for the teaching of geography have varied greatly over the centuries, questions in the conceptual and methodological scope related to geographic science directly reflect the organization of pedagogical work in this area of knowledge. Based on the critical educational approaches, an initial analysis is made of the main limitations and challenges that Geography teaching has been facing mainly in the educational and social function spheres. In the last decades the strong development of humanistic-cultural studies within geography has rekindled the discussions about the collaboration that the languages can offer to this science. Such discussions, in turn, show how the use of literature to foster criticality and provide teaching that distances itself from the traditional method can be used as an interdisciplinary model with efficiency. Faced with such arguments, the present research seeks to recover one of the closest literary manifestations of geography, which is the man's quest to know and understand the space that inhabits, such literature that had its apogee in nineteenth-century Europe, and which in France was very well represented by the writer Jules Verne, bring a novelized geographical vision while discussing matters of great importance with a critical approach. Through an analysis of the book The Invasion of the Sea, published in 1905, we explore the concepts, characteristics and geographic elements present in the narrative that provide us with evidence of the author's intimacy with the geography and themes related to it and which, in turn, can useful in school learning. This research, however, is more than a theoretical essay on the junction of literature and geography as a pedagogical aid to teaching; in order to better understand the benefits (or not) of this union, we propose to carry out a practical research with two schools of the state network of Mato Grosso - namely the Pascoal Moreira Cabral School and the Padre João Panarotto School, and to report the experiences obtained during two months where the book in question was read and discussed together with high school students in workshop format. Subsequent to the realization of the workshops, the analyzes carried out by the researcher both before and during and after the discussion period made it clear that there are many barriers that still need to be transposed into a learning linking different disciplines. It was also noticed that the use of vernian literature, although productive, needs a better preparation to be introduced in the school routine and, therefore, to be more useful to students' learning.This preparation in turn passes through the contemplation of the reading by the students to the extension of their vocabulary, perhaps being the case of starting to work with a simpler book. The difficulties, however, added up the benefits of a classroom model that runs counter to the traditional and evokes the imaginative capacity of students often repressed by tied teaching and without creative possibilities, in addition to the incentive given to reading within the school context and the vision of a geography that introduces itself more subtly through literature without ever ceasing to be scientific. In this way we have the opportunity to practice what we theorize through the deconstruction of a work by Jules Verne, and thus stimulate a teaching of Geography that gives students a critical- reflexive, emancipatory and at the same time pleasurable formation.